The Heat Exchange Mathematical Model of Fire in Cable Tunnel Adequacy Research - Nuianzin, Oleksandr; Samchenko, Taras; Kasiarum, Serhii; Hryhorenko, Kostiantyn; Kryshtal, Mykola (International Journal of Engineering and Technology, 2018)
According to the results of the conducted studies, the adequacy of the mathematical models of cable tunnels for their further use in the study of the temperature regime of the fire was checked. For this purpose, full–scale tests and findings about the dynamics of temperature change in cable tunnels with known geometrical parameters and fire load were conducted at the experimental test site of the Ukrainian Civil Protection Research Institute (Kyiv).In one of the CFD software systems, a mathematical model of a cable tunnel similar to the actual one was created. A computational experiment was conducted. Based on the results of the computational experiment and field tests, the criteria for adequacy (Student's t–criterion, Cochran's Q–criterion, Fisher's F–criterion) and the relative error of the experiments were calculated. On the basis of the analysis, the adequacy of the used mathematical models was studied.In this article, further development of the use of computational experiments to study the heat and mass exchange processes during fires in cable tunnels.